If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(c + -8) = 6 Reorder the terms: -1(-8 + c) = 6 (-8 * -1 + c * -1) = 6 (8 + -1c) = 6 Solving 8 + -1c = 6 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1c = 6 + -8 Combine like terms: 8 + -8 = 0 0 + -1c = 6 + -8 -1c = 6 + -8 Combine like terms: 6 + -8 = -2 -1c = -2 Divide each side by '-1'. c = 2 Simplifying c = 2
| -(c-8)=-124 | | -21+a=30 | | 5v^2-31v-28=0 | | 9n+3=5 | | 35x+80=24-90x | | y^2=x+4 | | 2v+7=1 | | 3(4s+7)=129 | | -2=x-(-5) | | 12x-30=4x-6 | | 2x-5y=42 | | 8y-8=4y-3 | | 6(2l+10)=192 | | C-(-3)=8 | | y=-4/9x-3=-7/5x-3 | | 2(a-8)=16 | | 9x-3Y=x+y | | x^2+1.8x-0.1516=0 | | 2n=36+-44 | | (q-8)*2=10 | | 3x+7=-7+2x | | 21=n+21 | | 5x+3x=7x+2x | | 5/6n=10 | | -16n=48 | | 170/33 | | N+17=6 | | 9x^2-4x-10=x-8 | | 15e=-45 | | 3/7n=-18 | | 3/7n=-19 | | (e+3)*4=24 |